Growth Performance of Different Tree Species in Agroforestry Systems in IGNP Command Area in Western Rajasthan - Singh, Bilas; Dhana Ram; Om Prakash; Deepak Kumar; Bhawana Sharma; Mana Ram Baloch (Annals of Arid Zone, 2024)
Tree integration in agriculture lands is climate resilient land use system traditionally practiced for improved productivity in arid regions. It enhances land productivity and improves livelihoods of rural dwellers. Four agroforestry models that includes block plantations of Prosopis cineraria (Khejri), Tecomella undulata (Rohida), grafted Zizyphus mauritiana (Ber) and Cordia myxa (Gunda) and boundary plantations of Dalbergia sissoo (Shisham), Carissa carandas (Karonda) and Cordia myxa were assessed at two sites within 500 m distance involving two farmers. Seedlings were planted in September 2021. Different crops were cultivated during kharif and rabi seasons of 2021 and 2022. Plants were measured for height and collar diameter and crop yields recorded. After two years of establishment, P. cineraria and T. undulata seedlings exhibited 99.0% survival, whereas seedlings of Z. mauritiana and C. myxa showed survival of 93.0% and 95.0%, respectively. Survival was relatively greater under block plantation as compared to the boundary plantations. Height and collar diameter growth of T. undulata was greater (p<0.05) by 87.0% and 37.0% than P. cineraria seedlings in agri-silvi model. Z. mauritiana exhibited 30.0% greater height, whereas C. myxa showed 22.7% greater collar diameter in agri-horti system. In boundary plantation, survival and growth was greater (p<0.05) in D. sissoo than C. carandas and C. myxa seedlings. Yield of Cyamopsis tetragonoloba was lesser than Plantago ovata and it was higher in 2022-23 than in 2021-22. However, dry matter and grain yields of both C. tetragonoloba and P. ovata were almost similar (p>0.05) in control as well as tree integrated plots. This indicated least competitive effect of trees on crops during initial 2 years. Conclusively, T. undulata and Z. mauritiana in agroforestry and D. sissoo in boundary plantation appeared suitable in initial years. However, recording of data for long term is suggested for effectual conclusion and recommendation based on tree crop interaction.